2017
DOI: 10.1002/pmic.201700033
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of Duck Tembusu virus (DTMUV)‐infected BHK‐21 cells

Abstract: Duck Tembusu virus (DTMUV) is a newly emerging pathogenic flavivirus that has caused huge economic losses to the duck industry in China since 2010. Moreover, the infection has spread rapidly, posing a potential public health concern. In this study, iTRAQ approach was first used to quantitatively identify differentially expressed cellular proteins in DTMUV-infected BHK-21 cells which are usually employed to produce veterinary vaccines for DTMUV, as well as other flaviviruses by serial passage. We identified 192… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…The JEV standard virus (Beijing strain) was provided by the Animal Vector‐Borne Disease Research Group, Department of Pathology, Faculty of Veterinary Science, Chulalongkorn University. The DK/TH/CU‐1 and JEV Beijing strain were propagated in baby hamster kidney (BHK‐21) cells as described previously (Sun et al., ; Teng et al., ). The viruses were harvested, clarified by centrifugation and the 50% tissue culture infectious doses (TCID 50 ) of viruses were calculated by the Reed and Muench method (Reed & Muench, ).…”
Section: Methodsmentioning
confidence: 99%
“…The JEV standard virus (Beijing strain) was provided by the Animal Vector‐Borne Disease Research Group, Department of Pathology, Faculty of Veterinary Science, Chulalongkorn University. The DK/TH/CU‐1 and JEV Beijing strain were propagated in baby hamster kidney (BHK‐21) cells as described previously (Sun et al., ; Teng et al., ). The viruses were harvested, clarified by centrifugation and the 50% tissue culture infectious doses (TCID 50 ) of viruses were calculated by the Reed and Muench method (Reed & Muench, ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several studies demonstrated the expression changes of several DDX proteins after DTMUV infection. Sun et al reported that DDX3X and DDX5 were significantly decreased in DTMUV-infected BHK-21 cells, and they found that DDX3X overexpression could inhibit DTMUV propagation by modulating the IFN-I via TBK1 protein [84], which was consistent with results showing duck DDX3X affecting DTMUV replication [101]. However, other quantitative proteomic analyses revealed that DDX5 was upregulated (1.84 fold) in DEF cells infected with DTMUV [102]; the result was different from DDX5 detection in mammalian cells, indicating that there might be a difference in the innate immune responses to DTMUV between avians and mammals.…”
Section: Other Prrs Relevant To Dtmuv Infectionmentioning
confidence: 99%
“…More importantly, the signaling proteins MyD88, TRAF3, and NF-κB were significantly upregulated [ 75 ], and DTMUV infection significantly increased the expression of IRF-1, indicating that the virus might induce MyD88 signaling pathway [ 83 ]. Differentially expressed proteins in DTMUV-infected BHK-21 cells were quantitatively identified by Sun et al by iTRAQ, the production of TLR9 increased at 48 hpi [ 84 ], which suggested that TLR9 can be potentially implicated in DTMUV infection in mammalian cell lines.…”
Section: Dtmuv Infection Triggers Host Innate Immune Responsesmentioning
confidence: 99%
“…Isobaric tags for relative and absolute quantification (iTRAQ) as a high-throughput proteomics approach are useful for the analysis of infection-associated proteins of pathogens [2224]. Sun et al [25] identified 192 significantly expressed host proteins in a DTMUV-infected baby hamster kidney cell line using the iTRAQ approach.…”
Section: Introductionmentioning
confidence: 99%